Antifungal Activity and Mode of Action of Miltefosine Against Clinical Isolates of Candida krusei - Wu, Yongqin; Wu, Mengying; Gao, Jing; Ying, Chunmei (Frontiers in Microbiology, 2020)
Candida krusei attracts attention from medical professionals mainly for its intrinsic resistance to fluconazole and the limited number of drugs available to treat C. krusei vulvovaginal candidiasis. Miltefosine was demonstrated to have good antifungal activity both in vitro and in vivo. Here, we determined the susceptibility profiles of 57 clinical C. krusei isolates from vulvovaginal candidiasis patients and assessed the antifungal activity of miltefosine against C. krusei. All isolates were susceptible to voriconazole and itraconazole, whereas 1.8% of the isolates were of non-wild-type phenotype to amphotericin B. In contrast, miltefosine showed low MICs against all C. krusei isolates with fungicidal activity. The checkerboard assay showed that the synergistic effect of miltefosine in combination with amphotericin B was observed in 25% of the tested planktonic C. krusei isolates and 18.8% of the tested preformed biofilms, whereas miltefosine in combination with fluconazole showed indifferent interaction for all tested planktonic isolates. The presence of sorbitol in the broth microdilution assay did not influence the MIC values of miltefosine against C. krusei, but the presence of ergosterol increased the MIC values. Visible changes in cell content in cells treated with miltefosine were observed. We found that cells treated with miltefosine showed decreased cell viability and chromatin condensation under PI staining, which indicates that miltefosine may induce apoptosis-like cell death in C. krusei. In conclusion, we found miltefosine has a good activity against C. krusei isolates and exerts its fungicidal effect by binding to ergosterol in the cell membrane and inducing apoptosis.